Joint precoding and user association for multiuser hybrid RF/VLC systems under secrecy constraints. - Silva, Isabella Wanderley Gomes Da [UNESP] (2022)
In this work, a joint strategy of precoding and user association for the direct link of hybrid radio-frequency (RF) / visible light communication (VLC) networks is investigated. Assuming a multiple-input single-output (MISO) system with VLC and RF access points (APs), and multiple users, where each user can connect only to the VLC or RF AP, we aim to maximize the sum secrecy rate of the network. First, an optimization problem to design a precoder that maximizes the sum secrecy rate of each AP is formulated. The precoding design is a non-convex fractional programming problem, which is extremely challenging to solve. For this purpose, the original problem is reformulated using the constrained convex-concave procedure (CCCP). The reformulated problem shows to be low-complex and can efficiently converge to an optimal solution. In addition, a user association algorithm based on the coalitional game theory is also proposed, to guarantee the maximum sum secrecy rate of the network. Numerical results emphasize the efficiency of the proposed joint precoding and user association (JPUA) method and its gain in terms of the network sum secrecy rate in comparison to different baseline schemes. Moreover, the number of iterations of the user association algorithm, and the effect of various system parameters, such as the transmit power and the total number of users connected to the network are also evaluated, highlighting the advantage of combining RF and VLC technologies.